Clinical And Radiological Features Of Extra-Pulmonary Sarcoidosis: Diagnosis And Management (The Review of Diabetic Studies, 2025)
Background: Sarcoidosis is a systemic illness of indeterminate etiology, pathologically defined by the aggregation of inflammatory cells that create non-caseating granulomas.Aim: This study aims at investigating the clinical and radiological features of extra-pulmonary sarcoidosis.Method: This study used a retrospective, observational cohort design at Al-Azhar hospitals in Egypt, focusing on adult patients aged 18 or older diagnosed with sarcoidosis through histological evidence. Patients will be recruited retrospectively from the hospital's records, meeting specific criteria. Data collected from eligible patients' medical records, including demographics, clinical presentation, radiological features, diagnostic procedures, management, and follow-up data. The study examined the relationship between clinical symptoms and radiological results, evaluate diagnostic paths, and assess therapy regimens. Ethical considerations will be considered, and approval will be obtained from the Institutional Review Board or Ethics Committee of the hospital.Results:Hematologic abnormalities were observed, with Group 2 exhibiting the lowest hemoglobin levels and the greatest white blood cell count.  The success of treatment was greatest for corticosteroids (82%), followed by biologics (74%) and immunosuppressants (66%). Oxygen therapy and lifestyle adjustments exhibited modest efficacy, whereas observation alone had the least effectiveness (28%).  The enhancement of kidney function was most significant in the immunosuppressant cohort, whereas parathyroid function exhibited the greatest improvement in the corticosteroid cohort. In addition an improvement in the rheumatological parameters was noticed among study groups.ConclusionSarcoidosis is a multisystem granulomatous disorder affecting the lungs, skin, eyes, neurological system, liver, and heart. It is more common in women and causes extra-pulmonary symptoms. Corticosteroids are effective in lowering calcium levels and rectifying metabolic abnormalities, while lifestyle adjustments and oxygen therapy provide moderate benefits. CT and HRCT is the main tools to diagnose sarcoidosis.